Reshoring: implementation issues and research opportunities - Ocicka Barbara (Management)
At the beginning of the 21st century, we continuously observe shifts in supply chains configurations caused by differentiate trends in turbulent environment. The remarkable number of companies restructure supply chains in search for competitiveness and innovation on global market. On the one hand, some labour-intensive industries are moving out of China to the next low-cost countries, on the other hand, some high-tech and innovative manufacturing companies are returning to the developed countries. The scientific purpose of the article is to set out the potential impact of reshoring on value creation in supply chains and to outline research opportunities in this field. Literature review and results of the questionnaire-survey on the Total Cost of Acquisition analysis are guidelines for considerations. Based on the analysis of reshoring drivers and benefits, it is clear that this strategy might have positive influence on the value creation in international and global supply chains management considering three dimensions of the value: economic, social and environmental from perspective of different stakeholders.